KARAKTERISTIK BAMBU ORI BANYUWANGI LAMINASI SUSUNAN BRICK DITINJAU DARI KEKUATAN TEKAN, TARIK, DAN LENTUR - Mirza Ghulam Rifqi; M. Shofi'ul Amin; Riza Rahimi Bachtiar; Dadang Dwi Pranowo; Habib Marjun Syafa'at (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2022)
Material engineering innovations are carried out to overcome problems. One of the problems is the use of wood material which in the harvest process takes a long time. Bamboo has a faster harvest time than wood with a harvest age of 3-5 years. However, bamboo is rarely used as a building material rather than wood because it has a hollow cylindrical dimension. Laminate Bamboo Technology makes bamboo dimensions like wood. Laminated bamboo is arranged into bricks using polyvinyl acetate (PVAC) adhesive with a blade thickness of seven mm. The bamboo lamination testing method refers to SNI-03-3958-1995, SNI-03-3399-1994, SNI 03-3959-1995, and SNI 03-3960-1995. Testing using Universal Testing Machine (UTM). The characteristics of the laminated Banyuwangi Ori bamboo with the brick arrangement in the wood classification include strong class II and quality code E25. The characteristics of Laminated Ori Bamboo are influenced by the character of the bamboo and the character of the glue.